Extracellular Lipase Production by Aspergillus niger Isolated From Industrial Oil Crops Using Submerged Fermentation - Issa, Qays Majeed (Journal of Pharmacology and Drug Development, 2025)
The screening, production, and optimization of extracellular lipase from a fungus Aspergillus niger isolated from different sources were examined in this work. The isolated fungi were screened on tributyrin hydrolysis method to detect exogenous lipolytic activity. A promising lipase producing isolate of A. niger-6 was selected and identified as the highest lipaseproducing strain. The optimal conditions were determined for: inducer oil, carbon source, nitrogen source, initial pH value, incubation temperature, incubation period, inoculum size, and shaking speed for lipase production using one factor at a time approach. Maximum lipase production was observed in 1% olive oil, 2% glucose, 2g/l ammonium sulphate, pH6, 30°C, 5days, 1x106spores/ml-1, and 150 rpm, respectively.